Ahmet Bey Agaoglu's views on society and citizens modern approach to analysis - Garanfil Guliyeva; Sevil Hasanova (Revista de Estudos Literários da UEMS - REVELL)
The article is devoted to the analysis of the ideas of Ahmet Bey Agaoglu, a prominent socio-political figure in the field of culture, literature, press, writer and writer of the late 19th and early 20th centuries. Ahmed Bey Agaoglu played an important role in the literary and public opinion and political life of our country in the 20th century as a public figure, publicist, politician, lawyer, scientist, and intellectual. In addition to a number of motifs, his ideas about society and citizens occupy an important place in his creativity. For the citizens of the free country described by the author, protection is both their right and their duty. A person who does not fulfill this duty with dignity and who turns a blind eye to injustice is punished together with the person who did this work. His activity and creativity played an important role in the socio-political processes in Azerbaijan, as well as in Europe, including the development of literary studies. In the activities of Ahmet Bey Agaoglu, his literary and scientific works occupy an important place; that is, he has historical and literary essays in addition to his works dedicated to social and political issues, which characterize him as a critic, literary critic and culturologist. . In his works, the author clearly and simply expresses his ideas, thoughts, wishes and desires about democracy, a democratic state and the place and role of people in society in this state.